Efficiency of Malaysian life insurance company using two-stage DEA method/ Nur Diyana Awanis Razaly ... [et al.] - Razaly, Nur Diyana Awanis; Saharuddin, Nurul Nadia; Mohamad Fauzi, Muhamad Faris Iskandar; Mohd Rashid, Nur Rasyida (Universiti Teknologi MARA, Perak, 2024)
The insurance industry provides unique financial services for the growth and development of every country. The efficiency measurement in the insurance companies may increase the quality of their operations and assist in identifying the inefficacy stages for future improvements. This research intends to evaluate the efficiency of 12 life insurance companies in Malaysia by applying the Traditional Data Envelopment Analysis (DEA) method as well as the Two-Stage DEA method in the year 2021. Traditional DEA views the actions of decision-makers as a black box, overlooking the intermediate process which is unsuitable for network systems in the insurance industry. The production process of a life insurance company is divided into two sub-processes, which are operational and profitability stages, suitable to be evaluated by the Two-Stage DEA method. This method calculates the efficiency score of the decision-making units (DMUs) by equally considering the intermediate phases. The model was executed using Lingo 20.0 software yielding efficiency scores ranging from 0 to 1. The findings revealed that five companies performed efficiently throughout the whole production process under Traditional DEA. However, none of these five companies has an overall efficiency score of 1 under the Two-Stage DEA. This is because none of those companies are efficient in both sub-processes. This reveals the limitations of Traditional DEA thus offers valuable insights to Malaysian life insurance companies on the effectiveness of Two-Stage DEA in assessing operational and profitability efficiencies. This study aids companies identify areas for improvement and encourage benchmarking against efficient competitors.